2021
DOI: 10.1108/bij-02-2021-0066
|View full text |Cite
|
Sign up to set email alerts
|

Competency framework to integrate lean construction and integrated project delivery on construction megaprojects: towards a future of work global initiatives in multinational engineering organisations

Abstract: PurposeBuilt environment organisations face global challenges between business units, especially since the coronavirus pandemic (COVID-19) has profoundly disrupted the construction industry worldwide, including the management of construction megaprojects (CMPs). This research aims to develop a competency framework, for global integrated delivery (GID) transformative initiatives and future of work (FOW) global initiatives, to manage integration between lean construction (LC) practices and integrated project del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 68 publications
0
36
0
Order By: Relevance
“…A number of recent research studies have discussed BIM, LC, IPD, LeanBIM, LeanIPD and LeanIPD&GID concepts, such as Evans et al (2021aEvans et al ( , 2021bEvans et al ( , 2021dEvans et al ( , 2021c, Evans and Farrell (2021). Moyo and Chigara (2021) determined barriers to LC implementation in developing countries and concluded that integration, performance, human capital management and quality are most significant barriers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent research studies have discussed BIM, LC, IPD, LeanBIM, LeanIPD and LeanIPD&GID concepts, such as Evans et al (2021aEvans et al ( , 2021bEvans et al ( , 2021dEvans et al ( , 2021c, Evans and Farrell (2021). Moyo and Chigara (2021) determined barriers to LC implementation in developing countries and concluded that integration, performance, human capital management and quality are most significant barriers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The current study is a continuation and progression of in-depth research. It critically appraises BIM, LC, IPD, LeanBIM, LeanIPD, LeanIPD&GID, competency behaviours, COVID-19 impacts and responses, GID, future of work (FOW) transformative initiatives and GID transformative initiatives by Evans et al (2021aEvans et al ( , 2021bEvans et al ( , 2021dEvans et al ( , 2021c, Evans and Farrell Lean construction and integrated project delivery (2021), Evans et al (2020aEvans et al ( , 2020a. Despite the apparent benefits of adopting the IPD approach in the USA and many countries worldwide, its implementation in the Middle East and North Africa (MENA) region faces a number of challenges that limit its adoption on megaprojects (Evans and Farrell, 2021;Rached et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Experts with between seven and fifteen years of successful experience in the construction industry were selected, with expertise in various forms of contracts and project delivery methods including IPD, and familiarity with digital information technologies such as BIM. Their awareness of IPD, and other emerging construction technologies and techniques, attests to the reliability of their responses within the framework of meeting the new-normal challenges based on IPD adoption in construction projects (Evans et al, 2021). The interviews were recorded, transcribed and coded by the first author to understand the evolution of projects before and after the beginning of the pandemic.…”
Section: Case Studiesmentioning
confidence: 99%
“…This program was aimed at training hospital employees and developing action plans to reduce their environmental impacts. Evans and Farrell (2020), Evans et al (2021d) and Evans et al (2021c) introduced global integrated delivery initiatives that integrate innovative construction methodologies such as lean construction concepts and building information modelling in integrative initiatives towards environmental sustainability for construction megaprojects, including hospitals. This included integration between building management systems (BMSs), innovative technologies, green procurement and integrated project delivery (Evans and Farrell, 2020; Evans et al , 2020a; Evans et al , 2020b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Energy issues have gained space on the agenda of governments and business managers worldwide and have become an essential topic in debates on environmental sustainability, global warming and the risk of the depletion of non-renewable sources, and the significant growth per capita energy consumption and global reliance on fossil fuels are all issues that are politically and commercially sensitive (AlQattan et al , 2018; Evans and Farrell, 2020; Evans et al , 2021d). Global warming and the risk of the depletion of non-renewable sources are directly related to the production of electricity.…”
Section: Introductionmentioning
confidence: 99%